Reproduções interpretativas de crianças sobre as relações entre escola e família - Costa, Áurea Júlia de Abreu (2019)
This thesis analyzes the interpretative reproductions of children about the tensions in the relationship between school and family, seeking to identify the conflicts that pass through this relationship and that appear in interactions between children and understand the children's negotiations carried out in the face of conflicts between school and family educational systems. The theoretical framework consists of the Historical-Cultural Theory, regarding the constitution of child subjectivity in interactions with adults, peers and elements of culture. The Sociology of Childhood also underlies this work by understanding childhood as a social category and children as children as social subjects who produce culture and they are also social agents who make interlocutions with the adult world, reproducing it interpretatively. Interpretative reproductions constitute the cultures of child peers and contribute to cultural transformations. The theoretical framework also consists of contemporary theorists of the sociology of education who discuss the social power relations that permeate the interactions between school and family. The school assumes the hegemonic and legitimate position, as opposed to children's cultures and family cultures that are considered illegitimate. The study is characterized as a qualitative research of ethnographic nature with participant observation in a school context of peer interaction and semi-structured interviews with parents and family members of the children. The survey was conducted with children who attended the first grade in 2017 and the second grade in 2018 in a municipal public school of kindergarten and elementary school located in the city of Fortaleza-Ceará. The children's interpretive reproductions pointed to the mismatches between family and school cultures, as well as to family issues that are interdicted or not directly addressed by children in the school context, and also to school charges on family assignments. The interactions between the children revealed the negotiations made regarding the dissonances between school and family, when there are conflicts between both institutions, but also when both coincide or approach each other. Interpretative reproductions emerged as compromise solutions in the face of deadlocks between school and family systems revealing peer culture as a symbolic space for the emergence of conflicts between children and between them and adults regarding to the ways of interpreting adult culture and adult world, as well as the contradictions between school and family. In addition, children’s peer culture appeared as a space for the collective construction of knowledge by children as well as space for negotiations with adults and validation of children's knowledge and resistance and children's agency to avoid adult ordinances. Children's peer culture also reveals itself as a space for the production of particular ways of dealing with the dissonance between school and family orders as well as dealing with family issues that are interdicted or not directly addressed by children in the school context and also with school charges on family assignments. It is concluded that the social participation of children in adult cultures (family and school) goes through listening to children and it offers subsidies for the construction of alteritarian practices between adults and children as educational pair as well as producing more democratic experiences of education and schooling, especially for children.